Mathematical Modelling of a Specialized Vehicle Caterpillar Mover Dynamic Processes Under Condition of the Distributing the Parameters of the Caterpillar - Strutynskyi, Serhii; Kravchu, Volodymyr; Semenchuk, Roman (International Journal of Engineering and Technology, 2018)
Features of a specialized vehicle caterpillar mover are considered. A dynamic model of caterpillar transverse oscillations as a system with distributed parameters is proposed. The differential equation in partial derivatives is obtained and its connection in the form of a decomposition by normal oscillation types is found. The analysis of frequencies and the type of caterpillar oscillations has been made. Inertial loads have been found. The mathematical model of forced oscillations of a caterpillar under the influence of random loads is developed and the mathematical modelling is executed. An analysis of the vibration movements and vibration velocities of the intersections of the caterpillar is carried out. The mathematical modeling of the caterpillar oscillations caused by stochastic discrete loads was carried out. A model of random discrete loads has been developed, calculations of the realization of random loads are performed. It was established that the transverse discrete loads occur in points of mass concentration on the caterpillar surface.Â